Quality of life and glycaemic control among older population with diabetes in three districts of Peninsular Malaysia - Shalihin, Mohd Shaiful Ehsan; Ahmad Zubaidi, Zati Sabrina; Mukhali, Hassan Basri; Md Aris, Mohd Aznan; Omar, Ahmad Marzuki; Aidid, Edre Mohammad; Fauzi, Abdullah; Fauzi, Nurul Afiqah; Abdul Aziz, Azrul Aziz (Malaysian Public Health Physicians' Association, 2023)
The older population is increasing in numbers worldwide. Most of them have multiple comorbidities including diabetes. The diabetic control in elderly is usually challenging. Their quality of life and socioeconomic condition either in rural or urban area could affect their disease progress. This study aims to measure the diabetic control and its associated factors, including quality of life among the older population with diabetes in three different districts of Malaysia. The patients’ health and background details were recorded. Validated Malay version of diabetes quality of life questionnaire was used. 485 elderly diabetic patients were recruited based on two proportion formula comprising all clinics in those districts representing urban vs rural area. Data were analyzed using simple and multiple logistic regression for the association. Only 30.5% of the patients have good diabetic control with patients in Kuala Terengganu district achieved better sugar control (p < 0.001). However, the only significant diabetic control predictor is the quality of life of the elderly patients (OR = 1.32, CI 1.047 – 1.224). Level of diabetes control in these three districts are poor, concomitant with the poor control of the elderly non-communicable disease profiles. It is essential to embark on holistic approach in dealing with the elderly diabetic management and identify measures to improve quality of life in those with poor glycaemic control in order to have better disease outcome.